Criminal Punishment under Russian Law of a Person for Failure to Report - Alexander V. Ostroushko3Liudmila A. Bukalerova1, Saule K. Amandykova2,; Mikhail A. Eliseev5Olga V. Avakova4, (Opción, 2019)
The aim of the study is to investigate the criminal punishment under Russian law of a person for failure to report on the existence of his second citizenship via the main provisions of the Russian science of criminal, migration, and international law. As a result, the guilty person is aware of the social danger of failure to fulfill the obligation. In conclusión, the crime provided by Article 330.2 of the Criminal Code of the Russian Federation, is deemed completed at the time of expiry in the period during which the person was obliged to file a corresponding notification.